PENGEMBANGAN KONSERVATIF GAMES IN AQUATIC UNTUK MENINGKATKAN KEBUGARAN JASMANI DAN SPORTIVITAS SISWA SEKOLAH DASAR - Bhayu Biliandri; Supriyono Supriyono; Agus Pujianto; Bambang Priyono (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
Physical Education, especially for increasing physical fitness, in the activities of implementing "Conservative Games in Aquatic", as the solution to physical education activities in the learning process at school. The products produced are also an additional reference for elementary school Physical Education teachers. Learning becomes more varied by using this product. In the research obtained results for the cognitive domain of 65% students in the category of Good While for the affective domain obtained 73% category Good, the assessment for the affective domain is based on student attitudes when implementing the game model, this can be seen from the attitude of students in the game. The overall Psychomotor domain of students is 81% Good category.